Pengaruh Kebijakan Investasi Dan Kebijakan Pendanaan Terhadap Nilai Perusahaan Pada Pt Pp (Persero) Periode 2015-2024 - Sasya Mariska Adelia; Vega Anismadiyah (Journal of Innovative and Creativity, 2026)
This study aims to analyze the effect of investment policy and financing policy on firm value at PT PP (Persero) during the 2015–2024 period. Firm value is proxied by Price to Book Value (PBV), investment policy is measured by asset growth, and financing policy is measured by the Debt to Equity Ratio (DER). This research employs a quantitative method using secondary data obtained from the annual financial statements of PT PP (Persero). The data analysis techniques include multiple linear regression analysis accompanied by classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results show that, partially, investment policy has a positive and significant effect on firm value, as indicated by a t-value of 3.636 which is greater than the t-table value of 2.365 with a significance level of 0.008 < 0.05. Financing policy also has a positive and significant effect on firm value, with a t-value of 2.537 which is greater than the t-table value of 2.365 and a significance level of 0.039 < 0.05. Simultaneously, investment policy and financing policy have a significant effect on firm value, as indicated by an F-value of 6.933 which is greater than the F-table value of 4.737 with a significance level of 0.022 < 0.05. The coefficient of determination (R²) of 0.665 indicates that 66.5% of the variation in firm value can be explained by investment policy and financing policy, while the remaining 33.5% is influenced by other variables outside the research model.